Hubungan Personal Factors Dan Interpersonal Influences Dengan Perilaku Merokok Pada Remaja Perempuan - Tryastuti, Dini; Widyaningsih, Fitriana Dwi (REAL in Nursing Journal, 2022)
Smoking is one of health problems that has not been resolved because the level of cigarette consumption is still high, this is evidenced by increase in the percentage of smoking from year to year in adolescent girls. Smoking behavior is influenced by several factors based on the Health Promotion Model theory. This study was to determine the relationship between personal factors and interpersonal influences with smoking behavior in adolescent girls. This study used an analytical survey method with a cross-sectional design. Kendall's Tau Correlation test is used as bivariate analysis. Questionnaire given to 119 adolescent girls in Cimanggis, Depok City, West Java with accidental sampling technique. The results showed that the majority of adolescent girls were light smokers (92.4%), there was no association between age with smoking behavior (Sig.2-tailed = 0.569), there was no association between income with smoking behavior (Sig.2-tailed = 0.587), there was no association between education level with smoking behavior (Sig.2-tailed = 0.505), there is a significant association between knowledge with smoking behavior (Sig.2-tailed = 0.000), there is a significant association between families with smoking behavior (Sig.2-tailed = 0.012), there is a significant association between peers with smoking behavior (Sig.2-tailed = 0.008), and there is a significant association between advertising media with smoking behavior (Sig.2-tailed = 0.012). Keywords: personal factors, interpersonal influences, smoking behavior, adolescent girls